THE ROLE OF ISLAMIC DOCTRINE IN PERSONAL DEVELOPMENT AND RELEVANT ISSUES - Nabiyev Muhrodbek Bobirovich (Web of Journals Publishing, 2025)
This article tells you about the Islamic source and Islamic faith in the development of the person as well as methods and advice of Islamic knowledge are included which can be used to bring up children.
Keywords: Personality, sociogenetic theory, biogenetic theory, personality development, personality composition, Islam, the law of recapitulation, role theory.